Preoperative prognostic nutritional index predicts postoperative delirium in aged patients after surgery: A matched cohort study - Song, Yu-Xiang; Wang, Qian; Ma, Yu-Long; Chen, Kun-Sha; Liu, Min; Zhou, Xue-Feng; Zhao, Hong; Lou, Jing-Sheng; Li, Hao; Liu, Yan-Hong; Mi, Wei-Dong; Cao, Jiang-Bei (General hospital psychiatry, 2024)
Prognostic nutritional index (PNI) is an indicator to evaluate the nutritional immune status of patients. This study aimed to assess whether preoperative PNI could predict the occurrence of postoperative POD in aged patients undergoing non-neurosurgery and non-cardiac surgery. The aged patients undergoing non-neurosurgery and non-cardiac surgery between January 2014 and August 2019 were included in the retrospective cohort study. The correlation between POD and PNI was investigated by univariate and multivariable logistic regression analysis, propensity score matching (PSM), inverse probability of treatment weighting (IPTW), and subgroup analysis. In the cohort (n = 29,814), the cutoff value of PNI was 46.01 determined by the receiver operating characteristic (ROC) curve. In univariate and three multivariable regression analysis, the ORs of PNI ≤ 46.01 was 2.573(95% CI:2.261–2.929, P < 0.001),1.802 (95% CI:1.567-2.071, P < 0.001),1.463(95% CI:1.246–1.718, P < 0.001),1.370(95% CI:1.165–1.611, P < 0.001). In the PSM model and IPTW model, the ORs of PNI ≤ 46.01 were 1.424(95% CI:1.172–1.734, P < 0.001) and 1.356(95% CI:1.223–1.505, P < 0.001). The PNI was found to have a predictive value for POD in patients undergoing non-neurosurgery and non-cardiac surgery. Improving preoperative nutritional status may be beneficial in preventing POD for aged patients.